Bioacoustic time capsules: Using acoustic monitoring to document biodiversity - Sugai, Larissa Sayuri Moreira [UNESP]; Llusia, Diego (Elsevier, 2019)
In the current extinction crisis, emerging technologies can support the urgent need to document biodiversity worldwide. Automated acoustic recorders are increasingly being used to remotely monitor species and soundscapes across the planet, generating a growing and valuable sound collection from present ecosystems. Such a collection can become a benchmark for future ecological research and shed light on our understanding of global change. Here we discuss the challenges and potential of acoustic monitoring to compose bioacoustic time capsules, environmental recordings capable to document, for future generations, how the planet's acoustic communities were in the past. For the present, acoustic monitoring can assist in ecological research and increase the chances of a species being detected, described, and hence protected. For the future, the collected time-series of audio recordings will compose bioacoustic time capsules, providing singular historical information on the structure and dynamics of past ecosystems and the activity of extinct fauna (acoustic fossils). Thus, we claim that acoustic monitoring should be included in biologist's toolbox to optimize the diligent task of documenting and protecting biodiversity.
Keywords: Audio recorder; Bioacoustics; Biodiversity loss; Conservation; Soundscape